Potential role of FKBP5 single‐nucleotide polymorphisms in functional seizures - Ali A. Asadi‐Pooya; Leila Simani; Marjan Asadollahi; Fatemeh Sadat Rashidi; Ehsan Ahmadipour; Afagh Alavi; Mehrdad Roozbeh; Nayyereh Akbari; Negar Firouzabadi (Epilepsia Open, 2023)
Abstract Objective We investigated the associations between FKBP5 single‐nucleotide polymorphisms (SNPs) and functional seizures (FS). Methods Seventy patients with FS, 140 with major depressive disorder (MDD), and 140 healthy controls were studied. Their DNAs were analyzed for the rs1360780 in the 3′ region and rs9470080 in the 5′ region of the FKBP5. Childhood trauma questionnaire and hospital anxiety and depression scale were used. Results Patients with FS and those with MDD had less GG and more AA genotypes in both rs9470080 and rs1360780 SNPs compared with those in healthy controls. Similar results were observed for allelic frequencies. There were no significant differences between FS and MDD groups in terms of genotype and allelic frequencies for both SNPs. The results of multinomial logistic regression analysis showed that FKBP5 polymorphisms were not associated with the diagnosis. Significance Patients with FS and those with MDD had significantly different genotypes in both rs9470080 and rs1360780 SNPs compared with those in healthy controls. However, it seems that FKBP5 polymorphisms were not associated with FS in the absence of depression. Further genetic investigations of patients with FS may increase our understanding of the neurobiological underpinnings of this condition, but such studies should be large enough and very well designed; they should include a comparison group with depression in addition to a healthy control group.